Impacts of stony coral tissue loss disease on the persistence of Caribbean cleaner gobies - Budd, Kayla A.; Sikkel, Paul C.; Brandt, Marilyn E.; Costa, Sophia V.; Smith, Tyler B.; Nemeth, Richard S. (Frontiers in Marine Science, 2024)
Because they serve as the main architects of coral reefs, the distribution and abundance of stony coral species have major impacts on other associated community members. Thus, coral diseases can have significant cascading effects throughout the ecosystem. Stony coral tissue loss disease (SCTLD) is the most recent of many diseases documented to impact Caribbean stony corals. SCTLD is known to impact over 20 species of reef-building corals and can cause complete colony mortality of large corals in only one month. Among the coral species impacted are those occupied as cleaning stations by Caribbean cleaner gobies. This study examined the persistence of these gobies on living coral cleaning stations where SCTLD was most recently or not yet affected (emergent), recently established (epidemic), and well-established (endemic),. Timed surveys were conducted at nine reefs in the U.S. Virgin Islands between October 2019 and March 2021. Study sites were surveyed both before and after the outbreak/establishment of SCTLD where possible. Monitoring sites were established at six reefs by tagging 25 live coral cleaning stations at each of two endemic and two epidemic sites and 50 cleaning stations at each of two emergent sites. Goby abundance at each site was monitored at least five times from March 2020 to April 2021. Timed surveys found cleaner goby abundance was 50% lower in the endemic zone compared to epidemic and emergent zones. Overall, goby abundance declined on tagged cleaning stations throughout the course of this study at all sites. However, overall goby density within monitored areas remained stable across most sites from the beginning to the end of the study. One emergent site experienced a two-fold increase in goby density and one epidemic site experienced a decline in goby density. This suggests that gobies are remaining at the site but may be abandoning live coral cleaning stations as the individual colonies are affected by SCTLD. Given the benefit cleaner gobies have on local coral reef fishes, changes in cleaning activity associated with coral disease have the potential to negatively impact Caribbean reef fish communities.